The development and electronic delivery of case-based learning using a fast healthcare interoperability resource system. Issue 4 (22nd October 2019) - Braunstein, Mark L; Oancea, Iulia; Barry, Benjamin K; Darlington, Sharon; Steel, Jim; Hansen, David P; Battock, James; Cheung, Daniel; Gan, Gregory; Hooper, Ben; Lundin, Reilly; Nicol, Duncan; et al.
Abstract: HL7 International's Fast Healthcare Interoperability Resources (FHIR) standard provides a common format for sharing health data (eg, FHIR resources) and a RESTful Application Programming Interface (eg, FHIR API) for accessing those resources via a FHIR server connected to an electronic health record system or any other system storing clinical data. Substitutable Medical Applications and Reusable Technologies (SMART) leverages FHIR to create an electronic health record (EHR) agnostic app platform. It utilizes the OAuth standard to provide for authorization and authentication. This paper describes the development and informal evaluation of Case Based Learning on FHIR (CBL on FHIR), a prototype EHR-connected FHIR/SMART platform to provide interactive digital cases for use in medical education. The project goals were to provide a more interactive form of CBL than is possible on paper to more realistically simulate clinical decision making and to expose medical students to modern informatics systems and tools for use in patient care.